Det halte begreb: ‘De idrætsusikre elever’ - Holt, Anne-Didde (Forum for Idræt, 2015)
Physical activity has important benefits for children’s health, but many children do not reach the recommended levels. The school setting provide a promising environment to increase children’s physical activity. In regards to that, politicians and scientists are especially focusing on a certain group of pupils, the so-called ‘sports insecure’ (‘idrætsusikre’). On the basis of a social constructionism theoretical framework, this article presents a critical analysis of the term ‘sport insecure’. The article draws on findings from a phenomenological-hermeneutic case study taking place in a multi-ethnic primary school in Denmark.